The Determinants Of Out-Of-Pocket Payments: Evidence From Selected Hospitals In Ankara, Turkey - Yıldırım, Jülide; Yılmaz, Erdoğan; GÜMÜŞOĞLU, NEBİLE KORUCU (Routledge Journals, Taylor & Francis Ltd, 4 Park Square, Milton Park, Abingdon Ox14 4Rn, Oxfordshire, England, 2011)
The aim of this study is to explore the determinants of the out-of-pocket expenditures on health in selected hospitals of the capital city Ankara, Turkey. Maximum likelihood logistic analysis is used to estimate the relationship between the likelihood of incurring out-of-pocket payments and a set of individual- and facility-level covariates, such as income, education level and wealth of the patient. Empirical findings indicate that as the level of education, age and income increase the likelihood of making out-of-payment expenditures on health increases. Additionally, the attitudes of patients towards the health-care system and their possible impacts on the decision of out-of-pocket payments have also been considered. The distrust in the public health-care system is reflected in patients' choices regarding the first applied medical centre. It appears that patients with high levels of income prefer private health-care rather than the public health-care services.